Adaptation of Digital Technologies in Secondary Level Education for Teaching English - Phunyal, Balkrishna (GS Spark: Journal of Applied Academic Discourse, 2023)
The government of Nepal's educational policy of Information Communication and Technology (ICT) emphasizes the need to adopt digital technologies such as the internet website, computers application, and ICT equipment in the context of secondary-level education for the efficiency of school education. This review paper examines the adoption of digital technologies in teaching and learning activities in secondary-level education in Nepal. This review and interview based paper addresses the challenges and opportunities that secondary-level English teachers faced during the process of teaching and learning process. It examines two possible explanations- first, the proper adoption of digital technologies in the field of education opens the way for opportunities for teachers and students, and second, teachers and students faced different challenges regarding the proper adoption of digital technologies which hinders effective and successful learning.It is argued that a sustainable way of implementing the ICT policy needs to be developed to mitigate the challenges raised during the process of adopting digital technology in education and provide adequate training to the teachers at the secondary level for the proper adoption of digital technologies. The adoption of digital technologies in secondary-level education in Nepal has both challenges and opportunities. A sustainable way of implementing the ICT policy needs to be developed to mitigate the challenges raised during the process of adopting digital technology in education and provide adequate training to the teachers at the secondary level for the proper adoption of digital technologies.